Estimativa de parâmetros genéticos, fenotípicos e ambientes para as produções de leite no dia do controle e em 305 dias de lactação de vacas da raça Gir - Ledic, Ivan Luz; Tonhati, Humberto [UNESP]; Verneque, Rui Da Silva; El Faro, Lenira; Martinez, Mário Luiz; Costa, Cláudio Nápolis; Campos Pereira, Jonas Carlos; Fernandes, Leonardo De Oliveira; Galvão De Albuquerque, Lúcia [UNESP] (My University, 2002)
Data from 32,779 monthly milk production, from 3,605 lactations until 305 days (PL305), from 2,082 Gir cows, sired by 281 bulls, calving from 1987 to 1999, in 11 herds, were used to verify the viability of using daily milk production control (PLDC) to perform genetic evaluations within Gir breed. Bivariate analysis on PLDC1 to PLDC10 and PL305 were performed utilizing the restricted maximum likelihood method within an animal model, which included the three first lactations as replicate measures of the same dams unit. Animals were grouped according to the criterion of contemporaneous group of herd-year-season, and according to calving-age and to the interval calving-first control in PLDC1. The observed averages (kg) and the respective standard deviations for PLDC1 at PLDC10 and PL305 were: 11.97±4.64; 11.93±4.68; 10.98±4.40; 10.18±4.12; 9.66±3.88; 9.20±3.69; 8.63±3.51; 8.08±3.33; 7.59±3.27; 7.22±3.15 and 2746.17±1299.90. The average lactation length was 273.72±48.95 days. Heritability estimates for PLDC based on bivariate analysis ranged from 0.24 to 0.14, decreasing from the first to the tenth control; the heritability estimate for PL305 was 0.19. Estimates of the genetic correlations between PLDC and PL305 varied from 0.85 to 1.00. The estimates of the genetic correlations between PLDC1 to PLDC9 with PLDC6 to PLDC10 were greater than 0.80, except the correlations between PLDC9 with PLDC1, PLDC10 with PLDC1, PLDC2, PLDC3 and PLDC6. The estimates of the phenotypic correlations resulting in intermediate value between genetic and environmental correlations (smaller). The results of genetic trend indicate that indirect selection for PLDC2 to PLDC4 was more efficient than direct selection for PL305.
Genetic, phenotypic and environmental parameters for milk production at the control day and 305 days of lactation of Gir breed cows
Keywords: Animal breeding; Dairy cattle; Milking control; Test day